The Development of the Grammar Material on the Basis of the Entrance Hypnosis Educational "Hypnoteaching" Android Program "Android" in the Course of the Intensive Arabic Language Course "Al Farisi" Pare Kadiri/تطوير مادة النحو على أساس مدخل التنويم المغناطيسيّ التعليمي "Hypnoteaching" ببرنامج أندرويد "Android" بدورة تعليم اللغة العربيةالمكثفة" الفارسي" باري كديري - Insia Angger (JURNAL IJ-ATL, 2018)
The objective of this research is to: 1 - Production of grammar on the basis of the entrance of educational hypnosis program in the course of the intensive Arabic language course "Persian" Bari, 2 - knowledge of the characteristics of the grammar based on the entrance of educational hypnosis program Android intensive Arabic language course "Al-Farisi" Pare, 3 - the effectiveness of the grammar material of the entrance to educational hypnosis program of the program of intensive Arabic language course "Persian" Barry. The researcher used quantitative approach, quantitative input and type of research and development. The tools for data collection are observation manual, interview manual, questionnaires, and testing. The most important results of this research: 1 - The preparation of educational materials in stages, namely: preliminary study, design, certification of experts, and experience in the field. 2. The characteristics of the developed product are: (a) the icon of the grammar program, (b) the introduction, (c) the main page containing the grammar, (d) the positive words on the basis of educational hypnosis; (G) the words of praise based on educational hypnosis, (h) the language used is simple for beginners, (i) exercises for grammar. 3 - The results of the product of the experts of this program is very good and these educational materials have a good effectiveness to improve the efficiency of students in the grammar in view of the rise of the rate of results from the tribal test 65.6 and then rose to 79 for the tribal test, as well as the result of the teacher and students after the use of on its use.يهدف هذا البحث إلى: 1- إنتاج مادة النحو على أساس مدخل التنويم المغناطيسيّ التعليمي ببرنامج أندرويد بدورة تعليم اللغة العربية المكثفة"الفارسي"باري،2- معرفة خصائص مادة النحو على أساس مدخل التنويم المغناطيسيّ التعليمي ببرنامج أندرويد بدورة تعليم اللغة العربية المكثفة"الفارسي"باري، 3- قياسفعّالية مادة النحو بمدخل التنويم المغناطيسيّ التعليمي ببرنامج أندرويد بدورة تعليم اللغة العربية المكثفة"الفارسي"باري.استخدمت الباحثة المدخل الكيفي والمدخل الكمي ونوع البحث والتطوير. والأدوات لجمع البيانات هي دليل الملاحظة، ودليل المقابلة، والاستبانة، والاختبار.وأهم نتائج هذا البحث : 1- وتمّ إعدادالمواد التعليميةعلى مراحل، وهي: الدراسةالتمهيدية، والتصميم، التصديق من الخبراء، والتجربةفيالميدان. 2- وأما خصائص المنتج المتطور، هي:(أ) الأيقونة لبرنامج مادة النحو، (ب) المقدمة، (ج) الصفحة الرئيسية التي تحتوي مادة النحو، (د) الكلمات الإيجابية على أساس التنويم المغناطيسي التعليمي، (ه) السؤال الدافع على أساس التنويم المغناطيسي التعليمي، (و)الساعة العاطفة على أساس التنويم المغناطيسي التعليمي، (ز)كلمات المدح على أساس التنويم المغناطيسي التعليمي، (ح) اللغة المستخدمة بسيطة للمبتدئين، (ط) التمرينات لمادة النحو. 3- كانت نتائج المنتج من الخبراء لهذا البرنامج وهي جيد جدا وهذه المواد التعليمية لها فعالية جيدة لترقية كفاءة الطلبة في مادة النحو بنظر من ارتقاء معدّل النتائج من الاختبار القبلي 65.6 ثم ارتقى إلى 79 للإختبار القبلي،  كذلك من نتيجة  استبانة  المعلم والطلبة بعد استخدامه هي وصالح على إستعماله.